Optimalisasi Perencanaan dan Penjadwalan Produksi: Kunci Meningkatkan Efisiensi Operasional - Lilis Setyowati; Untung Lasiyono (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2024)
Optimizing production planning and scheduling is a crucial aspect in improving operational efficiency in the competitive industrial era. This article discusses the importance of proper production planning and scheduling strategies to forecast demand and efficiently manage resource allocation, as well as effective scheduling to minimize downtime and increase throughput. The company has the possibility of not only providing better services to customers, but also reducing costs, and increasing efficiency, thus achieving a sustainable competitive advantage. This research uses a qualitative approach with a literature study method. The research was conducted by collecting information, then analyzed, and synthesized from various sources, including, journals, articles, and online publications.